Study of Instructional Model on Blended Learning in Polytechnic - Kadek Cahya Dewi; Putu Indah Ciptayani; Herman Dwi Surjono; Priyanto Priyanto (Jurnal Cakrawala Pendidikan, 2018)
Abstract: Polytechnic has characteristic which prioritizes the application of practical aspects supported by appropriate theory. Blended learning can be applied in Polytechnic, but a scheme is needed to formulate the correct instructional model. The study objectives were to examine the type of instructional model on blended learning that suits with Polytechnic. The research was conducted by qualitative descriptive approach by Miles and Huberman through observation, in-depth interview, Focus Group Discussion and literature review. The research validity was done by transferability, confirmability, credibility and dependability test. It can be concluded that the instructional model is appropriately determined by the suitability of educational model, technique and method of learning, and also facilities and infrastructure readiness. The instructional model on Blended Learning in Polytechnic is the Rotation Instructional Model. The study had implications on the learning process in Polytechnic. The lecturers could use the schema to determine the suit instructional model for their courses.Keywords: Instructional Model, Blended Learning, Polytechnic, Vocational Studi Model Instruksional pada Pembelajaran Kombinasi di PoliteknikAbstrak: Politeknik memiliki ciri khas pendidikan yang mengutamakan penerapan aspek-aspek praktis yang didukung oleh teori yang tepat. Blended learning dapat diterapkan di Politeknik, namun diperlukan sebuah skema untuk merumuskan instructional model yang tepat. Penelitian ini bertujuan untuk untuk mengkaji jenis instructional model pada Blended Learning yang sesuai dengan karakteristik pendidikan Politeknik. Penelitian dilakukan dengan pendekatan deskriptif kualitatif model Miles dan Huberman, teknik pengumpulan data observasi, wawancara, Focus Group Discussion dan kajian pustaka. Keabsahan data dengan uji transferability, confirmability, credibility dan dependability. Penelitian menyimpulkan bahwa instructional model yang tepat ditentukan dengan mempertimbangkan kesesuaian antara model pendidikan yang diselenggarakan, teknik dan metode pembelajaran mata kuliah, serta ketersediaan sarana dan prasarana pembelajaran. Sesuai dengan pertimbangan tersebut maka instructional model pada Blended Learning di Politeknik adalah Rotation Instructional Model. Implikasi penelitian terjadi pada proses pembelajaran di Politeknik. Para dosen dapat memanfaatkan instructional model skema untuk menentukan instructional model yang tepat untuk mata kuliah yang diampu.Kata Kunci: Instructional Model, Blended Learning, Politeknik, Vokasi